MODEL OF THE INFLUENCE OF EXOGENOUS SHOCK ON ORGANIZATIONAL AMBIDEXTERITY - Baptestone, Rolney Carlos; Costa, Ivanir; Martins, Fellipe Silva; Goes, Roberto; Stefani, Eduardo; da Silva Junior, Wanderley (PT Larva Wijaya Penerbit, 2025)
Purpose: This study examines how Exogenous Shocks affect Organizational Ambidexterity in VUCA and BANI environments, focusing on Information Technology's (IT) role in enhancing Absorptive Capacity and Crisis Perception. Design/methodology/approach: Using a quantitative approach, structural equation modeling (SEM) analyzed data from Brazilian IT professionals, with SMART-PLS software supporting the analysis. Findings: Exogenous Shocks significantly influence Organizational Ambidexterity. IT enhances Absorptive Capacity, aidy adaptation and innovation, and acts as a moderator in Absorptive Capacity. Research Limitations: The cross-sectional design limits causal inference, suggesting future research should explore longitudinal studies to deepen understanding. Practical Implications: Managers should invest in IT to boost responsiveness and resilience, fostering a culture of learning and innovation to exploit new opportunities and mitigate negative impacts. Originality: The study integrates organizational resilience and innovation within VUCA and BANI contexts, highlighting IT as a key facilitator for ambidexterity and innovation during crises.